2020
DOI: 10.1002/jclp.23079
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, efficacy, and daily coping and affect in depression over 6 months

Abstract: Objective: This study examined how perfectionism and efficacy impacted the maintenance of daily coping and affect in depression over six months.Method: Forty-six depressed patients (69.6% female, mean age = 41.11 years) completed measures of perfectionism dimensions (self-critical, personal standards), efficacy, and depressive severity at Time 1. Participants then completed daily diaries of stress appraisals, coping, and affect for 7 consecutive days at Time 1 and Time 2, 6 months later.Results: Perfectionism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Similar results were also observed in studies by Prud'homme & al. [45] and Richard & et al [46], also conducted with an adult (non-athlete) population. However, Castro & et al [47] showed that, in an adult student population of 344 individuals (non-athletes), the presence of NE was associated with a higher level of perfectionism, both adaptive and maladaptive (according to the models of Hewitt and Flett [19] and Frost & et al [36).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also observed in studies by Prud'homme & al. [45] and Richard & et al [46], also conducted with an adult (non-athlete) population. However, Castro & et al [47] showed that, in an adult student population of 344 individuals (non-athletes), the presence of NE was associated with a higher level of perfectionism, both adaptive and maladaptive (according to the models of Hewitt and Flett [19] and Frost & et al [36).…”
Section: Introductionmentioning
confidence: 99%